2012
DOI: 10.2527/af.2012-0062
|View full text |Cite
|
Sign up to set email alerts
|

Importance of cattle biodiversity and its influence on the nutrient composition of beef

Abstract: Abstract• Livestock make a substantial contribution to achieving food and nutrition security due to various factors including the high nutritional quality of animal-source foods.• Conservation and sustainable use of cattle genetic resources are important due to the multiple benefits provided by local breeds. These benefits include multiple direct uses, additional market value provided by specialty products, social and cultural roles, and adaptations that local breeds have to climate and diseases in harsh envir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…Therefore, an exhaustive overview on breed characteristics and product quality represents the starting point for the development of and the adherence to a preservation program (Verrier et al 2005;Canali 2006;Lauvie et al 2011). Aside from having a main role as a food source, local breeds also provide non-food benefits, such as grazing in areas that are unsuitable for crop production, maintaining the landscape (grazing activity, thus reducing the risk of fire and increasing wildlife biodiversity), and providing animal hair for the production of fibers (Gregory et al 2010;Barnes et al 2012). …”
Section: Introductionmentioning
confidence: 99%
“…Therefore, an exhaustive overview on breed characteristics and product quality represents the starting point for the development of and the adherence to a preservation program (Verrier et al 2005;Canali 2006;Lauvie et al 2011). Aside from having a main role as a food source, local breeds also provide non-food benefits, such as grazing in areas that are unsuitable for crop production, maintaining the landscape (grazing activity, thus reducing the risk of fire and increasing wildlife biodiversity), and providing animal hair for the production of fibers (Gregory et al 2010;Barnes et al 2012). …”
Section: Introductionmentioning
confidence: 99%
“…Compositional differences have been observed in local cattle breeds from developing countries. However, conclusions with respect to nutritional values between broadly-classified commercial and local breeds could not be drawn as, apart from breed diversity, management practices (such as diet and slaughter age) also affect the nutritional composition of the meat (Barnes et al, 2012). A study of two different pig genotypes, under identical nutritional and management conditions, has shown that there is variation between pig breeds in meat nutritional composition, for example in terms of intramuscular fat, dry matter, monounsaturated fatty acids, iron and zinc (Palma-Granados et al, 2018).…”
Section: Livestockmentioning
confidence: 99%
“…However, meat composition varies across species and breeds due to many factors of genetic and environmental origin. Therefore, the availability of data on the chemical composition of meat, determined in different breeds and taking into account the different sources of variation, is fundamental to better understand its role in the human diet [45].…”
Section: Chemical Composition and Nutritional Propertiesmentioning
confidence: 99%
“…However, when making comparisons, too-high values are sometimes reported as representative of beef [4,79], but they can be applied only to specific cattle breeds, such as those reared in countries where a high fat content is preferred [80]. Otherwise, the fat in buffalo meat is comparable to that of several dairy or beef bovine breeds, where values varying between 1.06% in the Asturiana breed and 3.21% in the Avilena breed are reported [45]. The situation may even be reversed in favour of beef if buffalo is compared to hypertrophied cattle breeds, characterised by very low amounts of fat [81][82][83].…”
Section: Chemical Composition and Nutritional Propertiesmentioning
confidence: 99%